Effectiveness of Digital Health Interventions in Improving Medication Adherence Among Individuals with Schizophrenia: A Systematic Literature Review - Hafidz Al Qodri (STIKep PPNI Jawa Barat, 2026)
Background: Medication non-adherence remains a major challenge in the long-term management of schizophrenia and is associated with relapse, psychiatric hospitalization, poor clinical outcomes, and increased healthcare costs. Digital health interventions have emerged as promising strategies to improve medication adherence; however, the available evidence remains heterogeneous across intervention types and healthcare settings. Objective: This systematic literature review aimed to synthesize and critically evaluate current evidence regarding the effectiveness of digital health interventions in improving medication adherence among individuals with schizophrenia and related severe mental illnesses. Methods: A systematic literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Electronic searches were performed in PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar for studies published between January 2022 and June 2026. Eligible studies evaluated digital health interventions designed to support medication adherence among individuals with schizophrenia or related severe mental illnesses. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools, and findings were synthesized using a narrative thematic approach. Results: The search identified 1,186 records, of which 20 studies met the eligibility criteria and were included in the review. The interventions included smartphone applications, mobile health (mHealth), telehealth, electronic medication monitoring systems, digital medicine systems, SMS reminders, and remote monitoring technologies. Overall, digital health interventions were associated with improved medication adherence, enhanced patient engagement, strengthened treatment monitoring, and better communication between patients and healthcare professionals. Nevertheless, the magnitude of these benefits varied according to intervention characteristics, study design, outcome measures, and healthcare settings. Common implementation barriers included limited digital literacy, inadequate technological infrastructure, and unequal internet access. Conclusion: Digital health interventions demonstrate considerable potential to improve medication adherence among individuals with schizophrenia and may strengthen continuity of care in mental health services. However, the heterogeneity of the available evidence highlights the need for further high-quality implementation research and pragmatic randomized controlled trials to evaluate long-term effectiveness and support sustainable integration of digital health into routine nursing practice.